Multi-omics combined with MALDI mass spectroscopy imaging reveals the mechanisms of biosynthesis of characteristic compounds in Tetrastigma hemsleyanum Diels et Gilg - Lin, Yan; Jiang, Xuechun; Zhu, Sheng; Dun, Junling; Pu, Jinbao; Liang, Weiqing (Frontiers in Plant Science, 2024)
Tetrastigma hemsleyanum Diels et Gilg is recognized as a source of extracts with various desirable bioactivities. However, current knowledge regarding the mechanisms of biosynthesis of flavonoids, phenolic compounds, and other bioactive chemicals is limited. We conducted comprehensive tissue distribution studies and biosynthetic analyses of the 26 main bioactive compounds of this plant. The majority of flavonoids exhibited higher concentrations in the cortex (CT) compared to the vascular cylinder (VC). The expression levels of genes and proteins in CT and VC were quantified using mRNA sequencing and isobaric tags for relative and absolute quantification (iTRAQ). A total of 31,700 genes were identified, among which 4921 exhibited differential expression between CT and VC. A total of 13,996 proteins were identified in the proteomes of CT and VC, with 927 showing differential expression. Co-expression network analyses of DEGs and DEPs from multiple sites demonstrated substantial pathway variations linked to flavonoid biosynthesis. Through differential enrichment analysis, a total of 32 genes involved in the flavone biosynthesis pathway were identified, with iTRAQ specifically detecting C3'H, F3H and FLS. Pearson correlation analysis revealed a strong association between the expression levels of C3'H, F3H, and FLS and the concentrations of flavonoids. The validation of multiple genes encoding pivotal enzymes was conducted using real-time fluorescence quantitative PCR (RT-qPCR). The findings provide a foundation for future investigations into the molecular mechanisms and functional characterization of T. hemsleyanum candidate genes associated with characteristic compounds.